Pengaruh Disiplin Mengajar Dosen Terhadap Motivasi Belajar Mahasiswa Program Studi Pendidikan Administrasi Perkantoran UNM - Sirajuddin Saleh; Muh. Nasrullah (Seminar Nasional LP2M UNM, 2019)
This study examines the effect of lecturer teaching discipline on student learning motivation in the FIS Office Administration Education Study Program at Makassar State University. The approach used in this study is a quantitative approach to the type of associative research. This research highlights two variables, namely lecturer teaching discipline (variable X) and student teaching motivation (Variable Y). The study population was all active students in the FIS Office Administration Education Study Program, Makassar State University, totaling 246 people from the 2016, 2017 and 2018 batches. While the study sample was 25% of the total population (62 people) taken using proportionale random sampling technique . Data collection techniques used were questionnaire technique, observation, and documentation techniques. Data obtained through a questionnaire instrument, were analyzed using descriptive statistics and inferential statistics. The results showed that: 1) The teaching discipline discipline of lecturers in the FIS Office Administration Education Study Program in Makassar State University was 75.17% and in the discipline category; 2) The description of student motivation in the Office of Education Administration Study Program FIS Makassar State University is 72.85% and is in the high category; 3) There is a positive and significant influence between the teaching discipline of lecturers on student learning motivation in the FIS Office Administration Education Study Program, Makassar State University